Cytological and comparative proteomic analyses on male sterility in Brassica napus L. induced by the chemical hybridization agent monosulphuron ester sodium - Cheng, Yufeng; Wang, Qian; Li, Zhanjie; Cui, Jianmin; Hu, Shengwu; Zhao, Huixian; Chen, Ming-Shun (My University, 2014)
Male sterility induced by a chemical hybridization agent (CHA) is an important tool for utilizing crop heterosis. Monosulphuron ester sodium (MES), a new acetolactate synthase-inhibitor herbicide belonging to the sulphonylurea family, has been developed as an effective CHA to induce male sterility in rapeseed (Brassica napus L.). To understand MES-induced male sterility in rapeseed better, comparative cytological and proteomic analyses were conducted in this study. Cytological analysis indicated that defective tapetal cells and abnormal microspores were gradually generated in the developing anthers of MES-treated plants at various development stages, resulting in unviable microspores and male sterility. A total of 141 differentially expressed proteins between the MES-treated and control plants were revealed, and 131 of them were further identified by MALDI-TOF/TOF MS. Most of these proteins decreased in abundance in tissues of MES-treated rapeseed plants, and only a few increased. Notably, some proteins were absent or induced in developing anthers after MES treatment. These proteins were involved in several processes that may be crucial for tapetum and microspore development. Down-regulation of these proteins may disrupt the coordination of developmental and metabolic processes, resulting in defective tapetum and abnormal microspores that lead to male sterility in MES-treated plants. Accordingly, a simple model of CHA-MES-induced male sterility in rapeseed was established. This study is the first cytological and dynamic proteomic investigation on CHA-MES-induced male sterility in rapeseed, and the results provide new insights into the molecular events of male sterility.
Citation: Cheng Y, Wang Q, Li Z, Cui J, Hu S, et al. (2013) Cytological and Comparative Proteomic Analyses on Male Sterility in Brassica napus L. Induced by the Chemical Hybridization Agent Monosulphuron Ester Sodium. PLoS ONE 8(11): e80191. doi:10.1371/journal.pone.0080191
Keywords: Brassica napus L.; Monosulphuron ester sodium; Rapeseed; Male sterility